Improvement of toon (Toona ciliata M. Roem.) genetic resources through growth and evaluation - Parthiban, K.T.; Krishnakumar, N.; Karthick, M.; Thirumurugan, M. (Indian Journal of Agroforestry, 2019)
Toona ciliata, a multipurpose tree species, is highly amenable for industrial agroforestry. A systematic tree improvement programme was initiated by selecting 23 progenies from its natural ranges distributed in Western Ghats of three Southern states of India. The progeny evaluation indicated that all progenies exhibited significant variation for height, diameter at breast height (DBH) and volume during three growth periods investigated and among them progenies evaluated, the superiority of progeny viz., TC02 was very well witnessed due to increased height (4.95 m), acceptable DBH (6.45 cm)and increased volume (0.010 m3). The growth attributes exhibited higher phenotypic coefficient of variance (PCV) values than their corresponding genotypic coefficient of variance (GCV) values. The heritability values were low ranging between 0.11 (clear bole height and number of branches) to 0.30 (plant height), and this could be due to juvenile period of evaluation. The association studies indicated the existence of positive and highly significant correlation between volume and clear bole height both at phenotypic (0.959) and genotypic (0.862) levels, and suggested that volume and clear bole height could act asreliable selection indices. The D2 analysis resolved 23 progenies into 7 clusters wherein the cluster V was largest with 12 progenies. The cluster distance indicated that cluster V registered maximum intra cluster distance (3.409) and the clusters VI and VII registered higher inter cluster distances (3.520) which exhibited existence of most heterogeneous population. Among growth attributes, volume contributed maximum towards genetic divergence (27.65 %), followed by clear bole volume (25.30 %). In a holistic perspective, the study identified early superiority of progeny TC02 in T. ciliata.